The association between dry needling-induced twitch response and change in pain and muscle function in patients with low back pain: a quasi-experimental study. Issue 2 (June 2017) - Koppenhaver, Shane L.; Walker, Michael J.; Rettig, Charles; Davis, Joel; Nelson, Chenae; Su, Jonathan; Fernández-de-las-Peñas, Cesar; Hebert, Jeffrey J.
Abstract: Objective: To investigate the relationship between dry needling-induced twitch response and change in pain, disability, nociceptive sensitivity, and lumbar multifidus muscle function, in patients with low back pain (LBP). Design: Quasi-experimental study. Setting: Department of Defense Academic Institution. Participants: Sixty-six patients with mechanical LBP (38 men, 28 women, age: 41.3 [9.2] years). Interventions: Dry needling treatment to the lumbar multifidus muscles between L3 and L5 bilaterally. Main outcome measures: Examination procedures included numeric pain rating, the Modified Oswestry Disability Index, pressure algometry, and real-time ultrasound imaging assessment of lumbar multifidus muscle function before and after dry needling treatment. Pain pressure threshold (PPT) was used to measure nocioceptive sensitivity. The percent change in muscle thickness from rest to contraction was calculated to represent muscle function. Participants were dichotomized and compared based on whether or not they experienced at least one twitch response on the most painful side and spinal level during dry needling. Results: Participants experiencing local twitch response during dry needling exhibited greater immediate improvement in lumbar multifidus muscle function than participants who did not experience a twitch (thickness change with twitch: 12.4 [6]%, thickness change without twitch: 5.7 [11]%, mean difference adjusted for baseline value, 95%CI: 4.4 [1 to 8]%). However, this difference was not present after 1-week, and there were no between-groups differences in disability, pain intensity, or nociceptive sensitivity. Conclusions: The twitch response during dry needling might be clinically relevant, but should not be considered necessary for successful treatment.